2011
DOI: 10.1155/2011/865634
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications after Thoracic Surgery in the Morbidly Obese Patient

Abstract: Little has been recently published about specific postoperative complications following thoracic surgery in the morbidly obese patient. Greater numbers of patients who are obese, morbidly obese, or supermorbidly obese are undergoing surgical procedures. Postoperative complications after thoracic surgery in these patients that can lead to increased morbidity and mortality, prolonged hospital stay, and increased cost of care are considered. Complications include difficulties with mask ventilation and securing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Most likely, as a consequence of the previously mentioned effects of obesity on lung physiology, frequently associated respiratory comorbidities and increased risk of atelectasis, obese surgical patients have a greater risk of respiratory failure and other postoperative pulmonary complications [ 73 , 113 ]. Several general care recommendations in the postoperative care of obese surgical patients have been proposed to decrease the risk of atelectasis [ 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most likely, as a consequence of the previously mentioned effects of obesity on lung physiology, frequently associated respiratory comorbidities and increased risk of atelectasis, obese surgical patients have a greater risk of respiratory failure and other postoperative pulmonary complications [ 73 , 113 ]. Several general care recommendations in the postoperative care of obese surgical patients have been proposed to decrease the risk of atelectasis [ 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with this evidence, in a large prospective study on patients undergoing general surgery intervention, obesity was found to determine a mild increased risk of wound infection only, whereas the incidence of major events did not differ from normal weight patients [29]. Increased body weight has an important impact on the respiratory physiology: dynamic lung volumes are reduced [30], and atelectasis persists longer in morbidly obese patients [31], thus leading to a potential increased risk of pulmonary complications [32]. This effect has been confirmed in a surgical series of patients submitted to lung resection for several conditions: obese patients developed a higher increase in alveolar-arterial oxygen difference and hypoxia [33], even though clinically relevant consequences did not occur more frequently among obese patients.…”
Section: Discussionmentioning
confidence: 88%
“…Another notable finding in this study was the significantly higher incidence of VTE and PE complications with rib fixation. Both obesity and surgery are risk factors for the development of PE [24, 34]. In many cases, VTE prophylaxis is often held before or after a planned surgical procedure despite the fact that trauma patients are at an increased risk for VTE [35], [36, 37].…”
Section: Commentmentioning
confidence: 99%